Małżeństwo w czasach reformacji: Małżeńskie normy prawne i sądownictwo małżeńskie w XVI wieku w świetle dokumentów z książęcych archiwów brzeskiego i legnickiego (2023)
MARRIAGE IN THE TIMES OF REFORMATION: NORMS OF THE MARRIAGE LAW AND MARRIAGE JUDICIARY IN THE 16TH CENT. IN LIGHT OF THE RECORDS OF THE ARCHIVES OF THE BRZEG AND LEGNICA DUCHIESThe source data concerning marriage norms and marriage judiciary as well as the types of related disputes on the territory of the three Duchies of Legnica, Brzeg, and Wołów under the rule of the dukes of the Legnica-Brzeg Piast Dynasty in the second half of the 16th century allow for the following recapitulation: The range of cases as revealed in the documents preserved in the archives of the Brzeg and Legnica Dukes are identifiable as matrimonial cases that had previously been heard by Church (bishop) courts and involved the validity and legality of the marriage. Most disputes in the period discussed seemed to have been brought about by the Reformation norms of marriage in three areas: making the validity of marriage dependent on parental consent, introduction of divorce, and a marriage contract as means of initiating the marital bond. As regards marriage judiciary, the research shows it was structured in several instances operating on the territories of the three abovementioned duchies. The last resort of the matrimonial judiciary formed in the 16th century was the ruler of the principality, the duke. He performed at least three functions in the matrimonial judiciary of the area. First, he was the one to appoint clergymen to act as matrimonial cases commissars within consistories. Second, he decided about the verdict and its announcement. Besides, he had an extraordinary power in marriage judiciary, being simultaneously the appellate instance with the power to grant dispensation, that is, a custom-made, unusual resolution in a given case.
Keywords: marriage in the 16th cent.; Luther about marriage; Protestant marriage law; marriage in the 16th cent. Silesia